[P078] System spatial resolution without scatter (NEMA): Preparing for measurement and calculations on gamma cameras with discrete pixel detectors. (August 2018) - Holzmannhofer, Johannes; Pirich, Christian
Abstract : Purpose: Quantitative measurements of performance characteristics of Gamma camera parameters have been specified[1] . Some of the tests are also applicable to discrete pixel detectors, sometimes requiring slight modifications to measurement and calculation: For system spatial resolution without scatter Siman and Kappadath[2] describe the use of several capillary tubes in staggered positions for each measurement. Using a high precision dovetail slide and only one capillary tube, measurements with arbitrary capillary tube position offset between each static acquisition can be realized. It has been also shown that measurements for discrete pixel detectors can be simulated using single crystal detectors. Methods: Several measurements were performed using a single crystal detector: An ensemble of static measurements consisted of displacing one capillary tube by a high precision dovetail slide in 1 mm steps over a distance of 10 mm. Pixel size (PS) used in each measurement ensemble: 0.6, 2.4 and 4.8 mm. System spatial resolution (FWHM, FWTM) was calculated according to[1] using MatLab. The ensemble of static measurements with a PS of 0.6 mm was used to calculate line spread functions corresponding to PSs of multiples of 0.6 mm (1.2, 1.8, 2.4, 3.0, …, 9.6) and the corresponding FWHM/FWTM using MatLab. Results: System spatial resolution for measured and calculated line spread function was: 4.47/4.38 mm (PS 0.6 mm), 4.76/4.73 mm (PS 2.4 mm) and 5.93/5.84 mm (PS 4.8 mm), respectively, indicating good agreement. Conclusions: Using a single capillary tube and a high precision dovetail slide for positioning permits arbitrary displacing (0.5 or 1.0 mm steps) between static measurements independent of the outer diameter of the capillary tube. Measurements and processing software for acceptance testing of a pixelated detector can be simulated using a single crystal detector with appropriate chosen pixel size.